Disruptive bodies and peripheral politics: How naked protests disrupt the patriarchal public sphere - Gassiep, Fadlah (Department of Political Studies, 2021)
On 4 October 2016, three black female students at the University of Witwatersrand (hereafter Wits) in Johannesburg, South Africa staged a naked protest to call for a ceasefire during the peak of the #FeesMustFall (FMF) protests. The FMF movement emerged in late 2015 as a student revolt against costly higher education fees especially for black students in South Africa. Armed police fired rubber bullets, stun grenades, and teargas to stop ongoing FMF protests which shut down university operations as students vowed to protest until all their demands were met. Within this context, the three female students at Wits University stood topless and formed a buffer zone between mostly male protesting students and the police. The method of protest was however mostly received with condemnation by the public and received widespread attention on social media platforms where the focus shifted from the central issues that sparked the naked protest to predominantly body shaming the women and questioning their morality (Ndlovu, 2017:68). This response to the naked protest therefore raised questions around the continuous policing of women's bodies and the patriarchal structure of public space where naked protests are performed. This thesis will use the 2016 naked protest that took place during violent FMF clashes between the police, private security, and students at Wits University as a lens to explore the ways in which naked protests have been used as an empowering tool to challenge men and authorities in violent contexts. It will draw on the 1990 naked protest in Soweto in South Africa, the 2002 naked peace protest in Liberia, and the 2002 anti-oil naked protest in Nigeria to illustrate the trajectory of naked protests in different African societies and the unique ways in which women's nakedness and undress has been perceived with apprehension in these societies. The central question that this thesis intends to explore is why do naked protests by women in African societies trigger apprehension in bystanders and black authoritarian male figures? I argue that it is a powerful form of protest, beyond cultural symbolisms attached to senior black women's bodies, as it subverts patriarchal mores underpinned in public space that delineates when and how black women can be seen in the public domain. I argue that it also provides the space for black women to assert their presence in protest movements and broader society which is typically unappreciated and overlooked. The point is to illustrate how naked protests ultimately undermines patriarchal mores and essentially invalidates colonial ideologies that renders the black female body socially invisible.